Pengaruh Brand Image Dan Kepercayaan Terhadap Keputusan Pembelian Produk La Omvi - Bagas Putra Aditya; Matdio Siahaan; Wirawan Widjanarko; Tungga Buana Irfana; Djuni Thamrin (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research was used to determine the influence of Brand Imgae, Trust on La Omvi Product Purchasing Decisions. This research is a quantitative research where the objects used are consumers who have purchased La Omvi products. The data used in the research are primary data using a questionnaire and secondary data sourced from books and journals by looking at the results of previous research. Determining the number of samples in this study used purposive sampling with the criteria of having purchased La Omvi products. The number of samples used in this research was 81 respondents. Data was processed using SPSS version 25 for Windows data analysis software. The results of this research show that Brand Image and Trust simultaneously influence the decision to purchase La Omvi products. The variable that has a more dominant influence on purchasing decisions is the Trust variable, this is shown by the Trust regression coefficient which is greater than the regression coefficient on Brand Image